Beneficial effects of curcumin in the diabetic rat ovary: A stereological and biochemical study - Tufekc, Kıymet; Kaplan, Suleyman (Springer Science and Business Media LLC, 2022)
Abstract
Study investigated the effects of curcumin treatment on diabetic ovaries at different periods of the disease. Fifty-six female Wistar albino rats (250–300 g) aged 12 weeks were divided into seven groups. No treatment was applied to the control group. The sham group was given 5 mL/kg of corn oil, and the curcumin group 30 mg/kg curcumin. In the DM groups, diabetes was induced by a single intraperitoneal dose of 50 mg/kg streptozotocin (STZ). The DM-treated groups received 30 mg/kg curcumin after either seven days (DC1 group), or 21 days (DC2 group), or simultaneously with STZ injection (DC3 group). Numbers of follicles in the ovaries were estimated using stereological method. FSH, LH, and SOD levels and CAT activity were measured in serum specimens. Follicle numbers and volumes of corpus luteum, blood vessel and cortex volumes, gonadosomatic index, and FSH and SOD levels all decreased significantly in diabetic ovaries, while relative weight loss, connective tissue volume, and CAT activity increased (p < 0.01). Curcumin treatment had a protective effect on the number of primordial follicles in the DC2 group and on antral follicle numbers in the DC3 group. Curcumin also exhibited positive effects on CAT activity and SOD levels, blood glucose levels, and corpus luteum, connective tissue and blood vessel volumes in the DC2 and DC3 groups. Curcumin also ameliorated FSH levels in the DC1 and DC3 groups (p < 0.01). Curcumin exhibits protective effects on ovarian structures and folliculogenesis, especially when used concurrently with the development of diabetes or in later stages of the disease.
Keywords: Curcumin; diabetes; Superoxide Dismutase; Ovary; follicle number; Antioxidants; Rats; Oxidative Stress; stereology; Diabetes Mellitus; oxidative stress; Animals; curcumin; Female; Antioxidant; Rats, Wistar; Follicle Stimulating Hormone; 3. Good health